Effects of fatuigue on postural control strategies during biathlon shooting - a nonlinear approach - Buchecker, M.; Sattlecker, G.; Birklbauer, J.; Wegenkittl, S.; Lindinger, S. J.; Müller, E. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
In biathlon shooting, stance stability represents an essential performance determining factor, and traditionally has been assessed by linear summary statistics of center of pressure (COP) time series (for references see Sattlecker et al., 2013). However, these tools neglect dynamical properties of the sway variability and, therefore, the aim of the current study was to re-analyze data of our group via nonlinear techniques in order to gain more profound insights into the motor strategies governing postural control in elite athletes.